2008
DOI: 10.1080/01419870701682238
|View full text |Cite
|
Sign up to set email alerts
|

Educational performance of native and immigrant children from various countries of origin

Abstract: Mostly due to the lack of suitable data, cross-national research on the integration of migrant pupils is still scarce. We aim to fill this gap by addressing the question of the extent to which native and first-and second-generation migrants from various regions of origin, living in thirteen different countries of destination, differ in their scholastic ability. Using the PISA 2003 data, we focus primarily on the impact of origin and destination effects on the scholastic achievement of migrants.The results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(76 citation statements)
references
References 13 publications
3
72
0
1
Order By: Relevance
“…Put another way, we expect that immigrants will feel less attached to a country in which various kinds of 'symbolic boundaries' (Lamont and Molnar 2002) are raised against them. One such boundary is anti-immigrant prejudice expressed by the non-immigrant population, with the straightforward expectation that immigrants will feel less attached to a society where such attitudes prevail.…”
Section: Ethnic and Racial Studies 2495mentioning
confidence: 98%
“…Put another way, we expect that immigrants will feel less attached to a country in which various kinds of 'symbolic boundaries' (Lamont and Molnar 2002) are raised against them. One such boundary is anti-immigrant prejudice expressed by the non-immigrant population, with the straightforward expectation that immigrants will feel less attached to a society where such attitudes prevail.…”
Section: Ethnic and Racial Studies 2495mentioning
confidence: 98%
“…Portes and MacLeod (1996) found for the United States that different migrant groups can present different advantages or disadvantages and that these effects remain after controlling for the socio-economic background. Levels and Dronkers (2008) showed that the immigrants' origins can have divergent impacts in different host countries. In contrast, Kristen and Granato (2007) observed in Germany that the socio-economic background removes the negative effect of origin.…”
Section: Comparing Compositional Effects In Education Systems 177mentioning
confidence: 99%
“…The relatively well-developed literature on education and labour market outcomes of immigrants in Western societies show that ethnic disadvantages persist even amongst the second generation born and grew up in a host society (Heath et al 2008). Apart from parental socioeconomic background which substantially explain ethnic inequalities (Levels and Dronkers 2008;Marks 2005), immigrant parents might also lack of fluency in host country language (Chiswick et al 2005;Dustmann and Fabbri 2003;van de Werfhorst and van Tubergen 2007) and knowledge in host country educational and labour market systems (Kristen 2008) which are crucial in socioeconomic achievement. Even though some immigrant parents are rich in socioeconomic resources in their country of origins, migration could disrupt intergenerational transfer of human, cultural and social capital between parents and children (Clark et al 2009).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%